INVESTIGATION AND DEVELOPMENT OF A CIGAR MADE WITH AROMATIC LEAVES FROM THREE REGIONS OF ECUADOR - Rodríguez Bustos, Joshue Alexander; Hurtado Bermeo, Diego Enrique; Mayorga Armendáriz, Carlos Andrés; Zabala Jarrín, Harold Alexi (mktDESCUBRE; Vol 1 No 3 (2020): Special Edition 1st International Marketing Congress, 2020)
The Ecuadorian tobacco industry has remained stagnant for the last decades, that is why this article aims to carry out research and development of a cigar with aromatic and tobacco leaves representative of each region of Ecuador, for this study the inductive method was used. deductive, bibliographic collection of books, scientific publications, journals and internet repositories, application of the Delphi method, use of the eyetracking tool, pilot survey and personal survey. The results obtained from the collection of information allows to know the current state of the Ecuadorian tobacco industry and the application of marketing concepts in said product, the Delphi method served to objectively analyze the competition while eyetracking allowed to know the points of attention of the Imagination, the preferential size of the cigar and more attractive packing areas, finally the results of the survey indicate that it is feasible to develop and launch the product to the market with an acceptance of seventy-five percent of the respondents, some alternatives are also presented of product communication including BTL advertising (Below the line) as Street Marketing. The investigation concludes with the creation of the cigar based on the results obtained from the market.